Access to a youth‐specific service for young adults with type 1 diabetes mellitus is associated with decreased hospital length of stay for diabetic ketoacidosis. Issue 4 (6th April 2018) - Burns, Kharis; Farrell, Kaye; Myszka, Rickie; Park, Kris; Holmes‐Walker, D. Jane
Abstract: Background: Management of type 1 diabetes mellitus in youth with diabetes (YWD) is complex, and glycaemic control often deteriorates during this challenging period. We hypothesise that attendance at a youth‐specific diabetes clinic reduces hospital admission rates and length of stay (LOS) for diabetic ketoacidosis (DKA). Aims: To assess the impact of a youth‐specific diabetes service for YWD on DKA admissions in two adjacent local health districts. Methods: A retrospective cohort analysis of admissions for DKA in YWD aged 15–25 years, presenting to four hospitals in Western Sydney in 2011 was performed. Number of admissions, LOS and DKA severity were assessed. Cost was analysed as a function of LOS. Groups were divided by attendance at a youth‐specific diabetes service and no record of attendance. Results: There were 55 DKA admissions from 39 patients (median age 20.0 years); the majority of admissions (82%) was YWD not supported by a youth‐specific diabetes service. Median LOS was significantly longer in the unsupported group (3.0 vs 1.5 days, P = 0.028). Median pH at presentation in the unsupported group was significantly lower, 7.11 versus 7.23 ( P = 0.05). The admission rate was four times greater for those not supported by youth‐specific diabetes services, 5.5% compared with 1.6% ( P = 0.001). The estimated cost saved by youth‐specific services was over $250, 000 pa. Conclusions: Lack of access to supported care for YWD during transition from paediatric to adult care has an adverse impact on subsequent DKA admission rates and LOS.